PENGEMBANGAN FLASHCARD BERBASIS AUGMENTED REALITY MELALUI MODEL ADDIE GUNA MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SD - Hidayat, Hidayat; Kena (LPMP Provinsi DKI Jakarta, 2025)
Conventional learning media such as textbooks and lecture methods are often considered less engaging and unable to optimally facilitate the development of critical thinking skills. This research uses the ADDIE model development research method, which is the development of augmented reality-based flashcard media. The purpose of this research is to develop AR media to improve critical thinking skills of elementary school students. The data collection technique in this research is validation from experts, namely media experts, language experts, and material experts, through interviews, observations, and tests to measure students' critical thinking skills. Data analysis was carried out by presenting data and drawing conclusions and quantitative data. The results showed that the use of Augmented Reality (AR) based flashcard s significantly improved students' critical thinking skills. Score increases occurred in all aspects, with Problem Identification increasing from 65 to 82, Data Collection from 68 to 77. This indicates that students are better able to recognize, process, interpret, and convey information. Overall, AR-based flashcards proved effective in improving critical thinking skills and making learning more interactive and engaging